The genetics of Psoriatic Arthritis - Butt, Christopher D., 1975- (2009)
Thesis (Ph.D.)--Memorial University of Newfoundland, 2010. Medicine Includes bibliographical references (leaves 216-293) Psoriasis is a stubborn chronic skin disease affecting 1-3% of the population. Although not life threatening, it may be associated with important morbidity and disability. Psoriatic Arthritis (PsA), an immunologically mediated disease, is an inflammatory form of arthritis usually seronegative for rheumatoid factor, which may affect as many as 30% of patients with psoriasis, thus up to 1% of the population may have PsA. Whereas the prevalence of inflammatory arthritis in the general population is estimated at 2 to 3%, in patients with psoriasis the prevalence of inflammatory arthritis varies from 6 to 42%. PsA is highly heritable with the risk ratio for siblings of PsA patients estimated at 30.8 times that of the general population. PsA is T-cell driven disorder and the pathogenesis derives from multiple processes including synovial and entheseal inflammation, angiogenesis, and altered bone remodelling. -- Association studies have repeatedly implicated the HLA-Cw*0602 loci of the Major Histocompatibility Complex (MHC) in the aetiology of PsA. Numerous other genes from several pathways have also been implicated in PsA. Using the unique population resource of Newfoundland, and a validation cohort from Toronto, it has been observed that there is an association between PsA and the MHC genes TNF-a and MICA. For the first time, an association has also been observed between PsA and the pro-angiogenic genes VEGF and PPARy. An association was also observed with the pleiotropic autoimmune gene PTPN22, and for the first time epistatic gene-gene interactions have been observed in PsA via a novel algorithm, adding further evidence to the central involvement of IL-23R in PsA.